Proceedings of the 2020 ACM Workshop on Intelligent Cross-Data Analysis and Retrieval 2020
DOI: 10.1145/3379174.3392318
|View full text |Cite
|
Sign up to set email alerts
|

Malware Detection Using System Logs

Abstract: Malware detection is one of the most critical features in many real applications, especially for the mobile platform and the Internet of Things (IoT) technology. Due to the proliferation of mobile devices and the associated app-stores, the volume of new applications growing extremely fast requires a better way to analyze all possible malicious behaviors. In this paper, we investigate the malware prediction problem using system log files that contain numbers of sequences of system calls recorded from IoT device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, the management and utilization of RM waste are necessary requirements for researchers and managers [1]. Several studies have reported the reuse of red mud in another industry such as for pigment [2] and fillers in polymer materials, among others [3][4][5][6][7][8]. Recently, there also have been growing interests of using red mud as a raw material for building materials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the management and utilization of RM waste are necessary requirements for researchers and managers [1]. Several studies have reported the reuse of red mud in another industry such as for pigment [2] and fillers in polymer materials, among others [3][4][5][6][7][8]. Recently, there also have been growing interests of using red mud as a raw material for building materials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%